USING NATIONAL ACTIVITY GAMES TO INCREASE INTEREST IN SPORTS AMONG SECONDARY SCHOOL STUDENTS (Multidisciplinary Journal of Science and Technology, 2025)
This article aims to use movement games as a means of physical education in the education of physical qualities in school-age children through the use of movement games, and on this basis to determine the theoretical foundations and methodological approaches to the technology of developing children's movement activity in general education schools, and to conduct research on the organization of physical education and mass health improvement activities carried out to develop children's movement activity in general education schools in the process of achieving this goal.